Astaxanthin alleviates oxidative stress and skeletal muscle damage by promoting mitochondrial biogenesis - Li, Chengmu; Yan, Yining; Wang, Kai; Jiang, Tao (Frontiers in Veterinary Science, 2025)
IntroductionThis study aimed to investigate the damaging effects of a high-fat diet (HFD) on mitochondria and skeletal muscle and to evaluate the protective role of astaxanthin (Asta), with a focus on mitochondrial biogenesis, oxidative stress, and inflammation under metabolic stress.MethodsHFD-fed mice and palmitate acid (PA)-stimulated C2C12 cells were treated with Asta. Skeletal muscle function, pathology, mitochondrial ultrastructure, inflammatory responses, and oxidative stress levels were assessed using behavioral tests, histology, quantitative reverse transcription-polymerase chain reaction, western blotting, transmission electron microscopy, and biochemical assays.ResultsAsta did not alter body weight or serum lipid levels in HFD-fed mice but markedly alleviated skeletal muscle damage and improved function. In both in vivo and in vitro models, Asta suppressed inflammatory gene expression, enhanced mitochondrial biogenesis-related proteins, reduced lipid accumulation and mitochondrial damage, increased antioxidant enzyme activity, and promoted ATP production. Furthermore, Asta inhibited mitochondrial fission and lipid peroxidation in PA-stimulated C2C12 cells.DiscussionAsta mitigates oxidative stress, lipid accumulation, and inflammation in skeletal muscle cells by promoting mitochondrial biogenesis, thereby preserving muscle structure and function. These findings highlight Asta’s potential as a therapeutic agent for skeletal muscle protection in metabolic stress conditions.